Band-gap-tunable CeO2 nanoparticles for room-temperature NH3 gas sensors. Issue 11 (1st August 2020) - Li, Pengpeng; Wang, Bing; Qin, Cong; Han, Cheng; Sun, Lian; Wang, Yingde
Abstract: NH3 is a type of essential raw material but harmful. In this work, CeO2 nanoparticles were synthesized as NH3 gas sensing materials by simple hydrothermal method. The response time of the sensor is extremely fast (3 s) towards 500 ppm NH3 with the response of 22.0 at room temperature. The concentration of NH3 and its response show well-matched functional relationship in the range of 0.5 ppm-1000 ppm. The selectivity of NH3 is distinct and the detection limit is as low as 500 ppb. The excellent NH3 gas sensing performance may be attributed to more oxygen vacancies and narrower band gap. This CeO2 nanoparticles-based gas sensor could be reliable to detect and monitor NH3 at room temperature.